Hydrogenation of furfural to tetrahydrofurfuryl alcohol over nickel-supported on organoclay catalyst - Kamble, Paresh A.; Vinod, C. P.; Rathod, Virendra K.; Kantam, Mannepalli Lakshmi (Applied Catalysis A-General, 2024)
Nickel supported on organoclay prepared by the impregnation method provides excellent catalytic activity for the hydrogenation of furfural to tetrahydrofurfuryl alcohol. The relative amount of metal and acidic sites influences the hydrogenation reaction. Additionally, by varying the temperature and the H-2 pressure, we can regulate the interaction of furfural with the active sites. And this may decide the fate of the reaction whether it will undergo a two-step hydrogenation to form tetrahydrofurfuryl alcohol or a rearrangement reaction to form cyclopentanone/cyclopentanol. Water was found to be the best solvent for the selective formation of tetrahydrofurfuryl alcohol. Even though alcohols inhibited rearrangement reaction, the hydrogenation of furfural was more selective towards furfuryl alcohol. Ni/O-clay30A under the optimum conditions of 120 degrees C, 4.0 MPa, and in 1 h offered complete conversion of furfural to tetrahydrofurfuryl alcohol.
Keywords: furfural; Hydrogenation; Nickel; organoclay; Tetrahydrofurfuryl alcohol